Heart rate variability, sleep quality and physical activity in medical students - Samuel Filipe Lopes Alves; Thaísy Andressa Bastos Primo de Sousa Santos; Marianne Lucena da Silva; Katiane da Costa Cunha (Sleep Epidemiology)
Aims: The present study aims to investigate the sleep quality, levels of physical activity, and their relationship with heart rate variability (HRV) in medical students. Methods: We conducted a cross-sectional study with 105 medical students from Brazil. Data were collected through sociodemographic questionnaires, Pittsburgh Sleep Quality Index (PSQI), International Physical Activity Questionnaire Short Form (IPAQ-SF), anthropometric measurements, and resting HRV. One-way ANOVA analysed sociodemographic variables, PSQI, and IPAQ scores. Spearman correlation assessed the relationship between anthropometric data and HRV parameters. Multiple Linear Regression examined the relationship between PSQI, IPAQ, and HRV, with a significance level of 5%. Results: A predominance of poor sleep quality and high physical activity levels were observed in medical students. Multivariate analysis revealed a significant association between HRV, IPAQ, and sleep quality in the SDNN (F reg=3.08; p = 0.0486) and LF (F reg=2.95; p = 0.0553) components. However, when analysing each variable independently, the correlation was statistically relevant only for the PSQI. The correlation was inversely proportional, indicating poorer sleep quality associated with lower HRV values. Conclusion: The results indicate that poor sleep quality is common among medical students and is correlated with a reduction in HRV, which may have an adverse impact on the cardiovascular health of this population.